Perbedaan Karakteristik Demografi dan Klinis Ibu Hamil Overweight dan Obesitas Tipe I - Reni Yuli Astutik; Nining Istighosah; Retno Palupi Yoni Siwi (AKADEMI KEBIDANAN DHARMA HUSADA KEDIRI, 2023)
Indonesia is also experiencing a nutritional transition, namely increased overweight and obesity. This trend has a big impact on both mothers and the babies born. There has been no research that reveals differences in the demographic and clinical characteristics of overweight and obese pregnant women, so appropriate management cannot be carried out according to the characteristics of pregnant women. The aim of this study is to explain the differences in demographic and clinical characteristics of overweight and obese type 1 pregnant woman in Kediri City.. This research uses a comparative analytical design. The research was conducted at nine Kediri City health centers, namely Campurejo, Banjarmlati, Pesantren I, Pesantren II, North Region City, South Region City, Ngletih, and Mrican health centers, from June to August 2023. The research population in June was composed of third-trimester pregnant women (102 pregnant women). Determining the sample using a simple random sampling technique, 86 pregnant women were obtained and divided into groups, namely overweight (n = 59) and type 1 obesity (n = 27). The research inclusion criteria include willingness to be a respondent, age 20–35 years, having ANC at least once in the first trimester and once in the second trimester, LILA > 23.5 cm, BMI > 25, and the exclusion criteria is pregnancy with comorbidities. Data analysis in this study used the Mann-Whitney, Fisher Exact, and Chi-Square tests with a significance value of 0.05 using SPSS 26. The research results showed that in the demographic characteristics of the overweight group compared to obesity type I, there were differences in age (p < 0.001), family history of obesity (p = 0.007), and there were no differences in education level (p = 0.0617), employment status (p = 0.096), income level (0.0353), and family support score (p = 0.587). Data on clinical characteristics in the overweight group compared to obesity type I showed differences in the history of hormonal contraceptive use (p = 0.049) and diet (p = 0.035), but there were no differences in gestational age (p = 0.157) or parity (p = 0.530). The differences in demographic and clinical characteristics between the two groups can be used as a reference for service providers so that pregnant women can control weight gain according to their body mass index.